An Analytic Model of Bond Risk Differentials - Bierman, Harold; Hass, Jerome E. (Journal of Financial and Quantitative Analysis, 1975)
There is broad consensus that three types of risk confront the potential bond purchaser: the risk of default (possible interest and/or principal loss), the risk of interest rate changes (possible principal loss or gain if the bonds are sold before maturity), and price level risk (loss of purchasing power). The analysis in this paper is directed toward the first of these risks, the risk of default. By assuming that investors require interest rate adjustments on debt subject to default sufficient to give them an expected present value equal to the present value associated with the investment of their funds in default-free securities, we examine the process that determines the risk-adjusted equilibrium interest rate and the factors affecting that rate. We also examine the implications of the model for the cost of debt and a firm's debt capacity.